(3WQGFb GdJOQjS GdYGeI hJWHjbGJgG GdJQHhjI (B/s - (3GdMehQj, eMehO YHO GdaJGMs; (3GdZGeOj, jhSas ((3GdOeGe, GdSYhOjI (B:s (3OGQ GHf GdLhRj ddfTQ h GdJhRjY,s, 2007)
(3GdJQHjI hGdJYdje, WQb GdJOQjS(B.s
(3HHdjhLQGajI (B: (3U(B. 194-200.s
Keywords: (3WQb GdJOQjSs